Appointing Arab Judges to the Courts in Israel, 1948–1969. Issue 1 (1st March 2019) - Lurie, Guy
Abstract : This article unveils a virtually unknown chapter in the history of judicial diversity in Israel. During its first 20 years of existence, between 1948 and 1968, only three Arab judges were appointed. Then, within two years, between 1968 and 1969, Israel appointed three additional Arab judges. Two interconnected changes account for this small increase in judicial diversity. First, in the 1960s, the Arab legal elite began to exert pressure on Israeli officials to appoint Arab judges. Second, perhaps partly due to this pressure, the Judicial Selection Committee made having a diverse judiciary a top priority. This historical example teaches us that without outside pressure, the Judicial Selection Committee does not look on diversity as an important consideration, using the merit system of appointment as an excuse for its failure. Indeed, up to the present day, the Israeli judiciary has relatively few Arab judges.